Networks and monumentality in the Pacific : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France), volume 7, session XXXVIII - Hermann, Aymeric,; Valentin, Frédérique,; Sand, Christophe,; Nolet, Émilie, 1978- (UISPP proceedings series ;, 2020)
This volume reflects the tremendous progress made in Pacific island archaeology in the last 60 years which has considerably advanced our knowledge of early Pacific island societies, the rise of traditional cultural systems, and their later historical developments from European contact onwards.